A case-control study of risk factors for infant mortality in a Brazilian municipality - Moreira, Leila Beltrami; Pessotto, Janine Gehrke (Clinical and Biomedical Research, 2024)
Introduction: Reducing infant deaths is a key objective of various national and international initiatives. Pato Branco is a Brazilian municipality located in the southwest of Paraná State. The city has had higher infant mortality rates than the State. In 2019, it had the worst rate in recent years (16.07/1000 live births). The study aimed to identify risk factors associated with infant mortality in Pato Branco/PR/BR from January/2013 to December/2019. Methods: We conducted a case-control study with data obtained from the Information System on Live Births (SINASC), the Mortality Information System (SIM), the Primary Health Care Information System (e-SUS APS), and a review of electronic medical records. The cases involved children who died between 2013 and 2019 before completing one year. Controls were selected among children born in the same hospital and on the same date, matched by sex, and who completed one year of life. Results: We included 103 cases and 206 controls. In a hierarchical conditional logistic regression model, absence of a steady partner (OR: 2.8), prenatal or childbirth complications (OR: 23.8), <7 prenatal visits (OR: 11.69), congenital anomalies (OR: 32.5), gestational age <37 weeks (OR: 7.4), Apgar <4 (OR: 17.6) and not having been breastfed (OR: 8.12) were risk factors for mortality, in the municipality. Lower education was a protective factor (up to elementary II - OR: 0.12; up to high school - OR: 0.26). Conclusion: Congenital anomalies, prematurity, and unfavorable perinatal conditions were associated with higher mortality, not differing from previous studies. The direct association between maternal education and the high rate of congenital anomalies deserves detailed investigation. This data suggests that social determinants of health may be context-specific, emphasizing the importance of conducting local studies.